2022
DOI: 10.1039/d2nr03275a
|View full text |Cite
|
Sign up to set email alerts
|

Inverse size-dependent Stokes shift in strongly quantum confined CsPbBr3 perovskite nanoplates

Abstract: We observe that different growth conditions and resulting morphologies of CsPbBr3 nanocrystals yield opposite stokes shift size-dependent trends. This emphasizes the different photo-physics for quantum-confined nanoplate and nanocube morphologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
(97 reference statements)
0
8
0
Order By: Relevance
“…The PL maximum of NRs and NWs is located at 460 nm, while for the NCs it is at 470 nm. The stock shift of NRs and NWs is rather low, which is mainly due to the 2D confined excitons in such systems . Furthermore, the PL maximum of NCs red-shifts as compared with NRs and NWs, which is due to the slightly larger NC size upon hole confinement in the valence band CsPbBr 3 nanocrystal .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The PL maximum of NRs and NWs is located at 460 nm, while for the NCs it is at 470 nm. The stock shift of NRs and NWs is rather low, which is mainly due to the 2D confined excitons in such systems . Furthermore, the PL maximum of NCs red-shifts as compared with NRs and NWs, which is due to the slightly larger NC size upon hole confinement in the valence band CsPbBr 3 nanocrystal .…”
Section: Resultsmentioning
confidence: 95%
“…The stock shift of NRs and NWs is rather low, which is mainly due to the 2D confined excitons in such systems. 27 Furthermore, the PL maximum of NCs red-shifts as compared with NRs and NWs, which is due to the slightly larger NC size upon hole confinement in the valence band CsPbBr 3 nanocrystal. 28 The PLQY of as-prepared NCs, NRs, and NWs is determined as 90%, 15%, and 24% respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results of inverse exciton Stokes shift dependence between the pure and Mn-alloy NPls as a function of the thickness (size) are nicely summarized in Figure e. Earlier inverse size-dependent Stokes shift was observed in CsPbBr 3 NPls compared to corresponding nanocubes, where a clear understanding remains blurred . It should be mentioned that in the literature sometimes researchers talk about the increase in Stokes shift upon Mn doping, which is basically the shift between exciton absorption and Mn PL emission .…”
mentioning
confidence: 75%
“…Earlier inverse size-dependent Stokes shift was observed in CsPbBr 3 NPls compared to corresponding nanocubes, where a clear understanding remains blurred. 44 It should be mentioned that in the literature sometimes researchers talk about the increase in Stokes shift upon Mn doping, which is basically the shift between exciton absorption and Mn PL emission. 27 However, this is not true exciton Stokes shift (but apparent Stokes shift) as the absorption states and emission states involve different species, and this is different from the present study.…”
mentioning
confidence: 99%
“…The Huang–Rhys factor reflects the strength of exciton–phonon interaction . Two-dimensional (2D) LHPs also exhibit broad emission characteristics assigned to the STE mechanism because of strong exciton–phonon coupling, as well as Stokes shifts of the free excitons due to quantum confinement effects. However, this explanation for broad emission is currently strongly debated, citing the existence of halide vacancy trap states. Using a combined experimental–computational study, Kahmann et al demonstrated that the broad emission in 2D LHP originates both from halide vacancies' trapped states and STE.…”
mentioning
confidence: 99%